Site-Selective Aliphatic C-H Chlorination Using N-Chloroamides Enables a Synthesis of Chlorolissoclimide - Quinn, Ryan K.; Koenst, Zef A.; Michalak, Sharon E.; Schmidt, Yvonne; Szklarski, Anne R.; Flores, Alex R.; Nam, Sangkil; Horne, David A.; Vanderwal, Christopher D.; Alexanian, Erik J. (Journal of the American Chemical Society, 2016)
Methods for the practical, intermolecular functionalization of aliphatic C-H bonds remain a paramount goal of organic synthesis. Free radical alkane chlorination is an important industrial process for the production of small molecule chloroalkanes from simple hydrocarbons, yet applications to fine chemical synthesis are rare. Herein, we report a site-selective chlorination of aliphatic C-H bonds using readily available N-chloroamides and apply this transformation to a synthesis of chlorolissoclimide, a potently cytotoxic labdane diterpenoid. These reactions deliver alkyl chlorides in useful chemical yields with substrate as the limiting reagent. Notably, this approach tolerates substrate unsaturation that normally poses major challenges in chemoselective, aliphatic C-H functionalization. The sterically and electronically dictated site selectivities of the C-H chlorination are among the most selective alkane functionalizations known, providing a unique tool for chemical synthesis. The short synthesis of chlorolissoclimide features a high yielding, gram-scale radical C-H chlorination of sclareolide and a three-step/two-pot process for the introduction of the beta-hydroxysuccinimide that is salient to all the lissoclimides and haterumaimides. Preliminary assays indicate that chlorolissoclimide and analogues are moderately active against aggressive melanoma and prostate cancer cell lines.